Effect of Adding Fermented Juice of Epiphytic Lactic Acid Bacteria Prepared From Different Sources And Levels of Soluble Carbohydrates on Chemical Composition, Fermentation And Quality Characteristics of Wheat Straw Silages (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:To improve the nutritional value of straw, which is available in large quantities as a byproduct of grain cultivation, the fermented juice of epiphytic lactic acid bacteria was used to enhance the fermentation of wheat straw silage, stimulate lactic acid production and improve Nutritional value of hay through anaerobic fermentation during silage.Materials and Methods:The fermented juice was prepared from wild reed with three sources of soluble carbohydrates and two levels for each source including glucose at level (1 and 2%, w/v) (A, B), cane molasses at (3 and 5%, w/v) (C, D) and date molasses at( 3 and 5%, w/v) (E, F) . According to this, Six samples of wheat straw silage prepared by adding fermented juice at a level of 1%. While distilled water was added in an amount similar to the amount of fermented juice when making the control group (G).Results:Results showed that addition fermented juice of epiphytic lactic acid bacteria improved (P